2004
DOI: 10.1136/oem.2002.006932
|View full text |Cite
|
Sign up to set email alerts
|

Six year observational cohort study of the effect of carbon disulphide on brain MRI in rayon manufacturing workers

Abstract: Aims: To clarify whether the current occupational exposure limit (OEL) for carbon disulphide (CS 2 ) is low enough to prevent the occurrence of adverse effects on the cerebrovascular system. Methods: A total of 432 male workers exposed to CS 2 and 402 male referent workers in 11 Japanese viscose rayon factories were studied at baseline; 750 of these were followed up. Brain MRI was performed at both baseline and follow up surveys. Changes in the number of hyperintense spots in T2 weighted images (HIS), which po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 24 publications
(23 reference statements)
1
15
0
Order By: Relevance
“…Those with any history of chronic disease such as hypertension, diabetes mellitus, stroke, and cardiovascular disease were excluded from the study at baseline. Details of the study and the results of the cohort study have been described elsewhere (19,20). To investigate the effects of job strain on arteriosclerosis, we added a questionnaire in the follow-up survey of 1998−1999.…”
Section: Study Populationmentioning
confidence: 99%
“…Those with any history of chronic disease such as hypertension, diabetes mellitus, stroke, and cardiovascular disease were excluded from the study at baseline. Details of the study and the results of the cohort study have been described elsewhere (19,20). To investigate the effects of job strain on arteriosclerosis, we added a questionnaire in the follow-up survey of 1998−1999.…”
Section: Study Populationmentioning
confidence: 99%
“…Second, there was a lack of information on previous CS2 exposure concentration. In general, exposure concentrations to hazardous chemicals have been improved by the introduction of effective industrial hygiene control measures in occupational settings, as shown in our previous studies [4][5][6] . The most important question is whether the increased risk that we observed was caused by previous or recent exposure.…”
Section: Discussionmentioning
confidence: 66%
“…This result indicates that not only previous exposure but also recent exposure had some impact on SCV of the median nerve in this population. Third, although long peripheral nerves, such as the sural nerve, may be more suitable to evaluate the effects of neurotoxins, we measured NCV of the median nerve only due to the limited time allowed for comprehensive health checkups, including examinations of sclerosis of the carotid and aortic arteries, at rest and exercise ECG, ophthalmological test, neurobehavioral examinations, and NCV test at the rayon factories [4][5][6] . If we could examine the long nerves, we could have observed clearer outcomes than those in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations